V2 hotspot optimized MVA vaccine expressing stabilized HIV-1 Clade C envelope Gp140 delays acquisition of heterologous Clade C Tier 2 challenges in Mamu-A*01 negative Rhesus Macaques - Styles, Tiffany M.; Gangadhara, Sailaja; Reddy, Pradeep B. J.; Sahoo, Anusmita; Shiferaw, Ayalensh; Welbourn, Sarah; Kozlowski, Pamela A.; Derdeyn, Cynthia A.; Velu, Vijayakumar; Amara, Rama Rao (Frontiers in Immunology, 2022)
Stabilized HIV envelope (Env) trimeric protein immunogens have been shown to induce strong autologous neutralizing antibody response. However, there is limited data on the immunogenicity and efficacy of stabilized Env expressed by a viral vector-based immunogen. Here, we compared the immunogenicity and efficacy of two modified vaccinia Ankara (MVA) vaccines based on variable loop 2 hotspot (V2 HS) optimized C.1086 envelope (Env) sequences, one expressing the membrane anchored gp150 (MVA-150) and the other expressing soluble uncleaved pre-fusion optimized (UFO) gp140 trimer (MVA-UFO) in a DNA prime/MVA boost approach against heterologous tier 2 SHIV1157ipd3N4 intrarectal challenges in rhesus macaques. Both MVA vaccines also expressed SIVmac239 Gag that forms virus-like particles. The DNA vaccine expressed SIVmac239 Gag, C.1086 gp160 Env and rhesus CD40L as a built-in adjuvant. Additionally, all immunizations were administered intradermally (ID) to reduce induction of vaccine-specific IFN+ CD4 T cell responses. Our results showed that both MVA-150 and MVA-UFO vaccines delivered ID induce comparable Env specific IgG responses in serum and rectal secretions. The vaccine induced serum antibody showed ADCC and ADCVI activities against the challenge virus. Comparison with a previous study that used similar immunogens via intramuscular route (IM) showed that ID immunizations induced markedly lower SHIV specific CD4 and CD8 T cell responses compared to IM immunizations. Following challenge, MVA-UFO vaccinated animals showed a significant delay in acquisition of SHIV1157ipd3N4 infection but only in Mamu A*01 negative macaques with an estimated vaccine efficacy of 64% per exposure. The MVA-150 group also showed a trend (p=0.1) for delay in acquisition of SHIV infection with an estimated vaccine efficacy of 57%. The vaccine-induced IFNsecreting CD8 T cell responses showed a direct association and CD4 T cells showed an inverse association with delay in acquisition of SHIV infection. These results demonstrated that both MVA-150 and MVA-UFO immunogens induce comparable humoral and cellular immunity and the latter provides marginally better protection against heterologous tier 2 SHIV infection. They also demonstrate that DNA/MVA vaccinations delivered by ID route induce better antibody and lower CD4 and CD8 T cell responses compared to IM.